Comparison of Subjective Dizziness, Tinnitus, Headache, Taste, and Smell Results by Age Group in Yakumo Town Residents Health Checkup Conducted in 2019 with Measured Taste and Smell Test Results (Global Journal of Medical Research, 2023)
Abstract not found
Keywords: yakumo study; olfactory function test; taste test; the prevalence of vertigo; the prevalence of tinnitus